2020
DOI: 10.1038/s41598-020-58833-7
|View full text |Cite
|
Sign up to set email alerts
|

Holographic molecular binding assays

Abstract: We demonstrate that holographic particle characterization can directly detect binding of proteins to functionalized colloidal probe particles by monitoring the associated change in the particles’ size. This label-free molecular binding assay uses in-line holographic video microscopy to measure the diameter and refractive index of individual probe spheres as they flow down a microfluidic channel. Pooling measurements on 104 particles yields the population-average diameter with an uncertainty smaller than 0.5 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Holographic microscopy has recently been demonstrated as being sensitive enough for this task. 176 One of the inventors of the technique has suggested that it can be used for detecting antibodies from COVID-19 infection or whole virions of SARS-CoV-2. 177 For completeness, we mention the state of aggregation of viruses, which must be known, e.g., in order to understand the meaning of viral titre measurements in terms of plague forming units.…”
Section: Detectionmentioning
confidence: 99%
“…Holographic microscopy has recently been demonstrated as being sensitive enough for this task. 176 One of the inventors of the technique has suggested that it can be used for detecting antibodies from COVID-19 infection or whole virions of SARS-CoV-2. 177 For completeness, we mention the state of aggregation of viruses, which must be known, e.g., in order to understand the meaning of viral titre measurements in terms of plague forming units.…”
Section: Detectionmentioning
confidence: 99%
“…Measurements on emulsion droplets demonstrate precision and reproducibility in the refrac-tive index of ±1 part per thousand [27]. The former is fine enough to detect the formation of a molecular coating on a bead through the associated change in the bead's diameter [5,28]. The latter is useful for distinguishing different types of beads on the basis of their composition [29].…”
Section: Holographic Particle Characterizationmentioning
confidence: 99%
“…Holographic particle characterization [1] is a fast and robust technique for measuring the size and refractive index of colloidal spheres and has a wide variety of applications in basic research [2][3][4][5], industrial materials analysis [6] and medical diagnostics [5,7]. As illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Holographic particle characterization works by recording the in-line hologram of a colloidal particle [1] and then analyzing it pixel-by-pixel [2] with a generative model based on the Lorenz-Mie theory of light scattering [3][4][5]. This analysis yields the particle's diameter with nanometer-scale precision and its refractive index to within a part per thousand [2,6], which should be fine enough to detect nanometer-scale molecules binding to the surfaces of micrometer-scale colloidal beads [7,8]. The resulting label-free assay for molecular binding, shown schematically in Fig.…”
Section: Introductionmentioning
confidence: 99%